2005
DOI: 10.1126/science.1110656
|View full text |Cite
|
Sign up to set email alerts
|

Endosomal Proteolysis of the Ebola Virus Glycoprotein Is Necessary for Infection

Abstract: Ebola virus (EboV) causes rapidly fatal hemorrhagic fever in humans and there is currently no effective treatment. We found that the infection of African green monkey kidney (Vero) cells by vesicular stomatitis viruses bearing the EboV glycoprotein (GP) requires the activity of endosomal cysteine proteases. Using selective protease inhibitors and protease-deficient cell lines, we identified an essential role for cathepsin B (CatB) and an accessory role for cathepsin L (CatL) in EboV GP-dependent entry. Biochem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

40
970
6
6

Year Published

2005
2005
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 770 publications
(1,032 citation statements)
references
References 23 publications
(22 reference statements)
40
970
6
6
Order By: Relevance
“…2). By affecting either viral entry 31,32 or exit 33,34 , these and other proteases could influence viral cellular tropisms and perhaps interactions between glycoprotein domains and antibodies (FIGS 2,3). Moreover, Barrientos and Rollin reported recently that endosomal proteolytic enzymes, including cathepsins, were released from EBOV-infected cells, that this release was more pronounced in cells infected with a more lytic variant of EBOV and that cytopathicity was diminished by the cathepsin inhibitor E64 (REF.…”
Section: Box 1 | Filovirus-disease Basicsmentioning
confidence: 99%
“…2). By affecting either viral entry 31,32 or exit 33,34 , these and other proteases could influence viral cellular tropisms and perhaps interactions between glycoprotein domains and antibodies (FIGS 2,3). Moreover, Barrientos and Rollin reported recently that endosomal proteolytic enzymes, including cathepsins, were released from EBOV-infected cells, that this release was more pronounced in cells infected with a more lytic variant of EBOV and that cytopathicity was diminished by the cathepsin inhibitor E64 (REF.…”
Section: Box 1 | Filovirus-disease Basicsmentioning
confidence: 99%
“…Chandran et al (2005) performed in vitro experiments in the Vero cell line derived from the African green monkey kidney using recombinant vesicular stomatitis viruses expressing EBOV GP and showed that cysteine proteases are important for the proteolytic processing of the EBOV GP in the endosome, which facilitate EBOV entry into the cells, and CatB plays an essential role in this process. It was demonstrated that a synthetic CatB inhibitor, CA074, suppressed the proteolysis and viral replication following infection with the Zaire strain of EBOV (ZEBOV) (Chandran et al 2005). These findings presented that protease inhibitors that can effectively suppress CatB may be beneficial for treatment of EVD.…”
Section: Effects On Catb and Ebov Replicationmentioning
confidence: 99%
“…The processing is considered to prime the fusion as shown in Fig. 1 (Chandran et al 2005). In brief, a substantial portion of GP 1 is initially removed by CatL, which is then trimmed into a smaller form by CatL and/or CatB and is cleaved to a still smaller form by CatB.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations